The Effect of Entrepreneurship Orientation and Market Orientation on Msmes in the Culinary Fields Through Personal Excellence - Jently F. Tamailang; Allen Ch. Manongko; Lihard S. Lumapow; Edwin Wantah (Syntax Corporation Indonesia, 2021)
his study aims to determine the direct and indirect effects of entrepreneurial orientation, market orientation, and competitive advantage on the performance of SMEs in the culinary field. The method used in this study is a quantitative method with path analysis techniques. The results of this study are: 1), entrepreneurial orientation has a positive and significant direct effect on the competitive advantage of SMEs. That is, if the entrepreneurial orientation increases, the competitive advantage will increase. 2), market orientation has a positive and significant direct effect on the competitive advantage of SMEs. That is, if market orientation increases, then competitive advantage will increase. 3), entrepreneurial orientation has a direct and positive effect on the performance of SMEs. That is, if the entrepreneurial orientation increases for the better then the performance will increase for the better. 4), market orientation has a direct and positive effect on the performance of SMEs. That is, if the market orientation improves, the performance of MSMEs will increase. 5), competitive advantage has a positive and significant direct effect on the performance of SMEs. That is, if competitive advantage increases, the performance of SMEs will increase. 6), entrepreneurial orientation has no significant effect on the performance of SMEs through competitive advantage. That is, competitive advantage cannot be an intervening variable for the effect of entrepreneurial orientation on the performance of SMEs because the direct effect of entrepreneurial orientation on the performance of SMEs is greater than the effect of entrepreneurial orientation. SME performance through competitive advantage. 7), market orientation has no significant effect on the performance of SMEs through competitive advantage. That is, competitive advantage cannot be an intervening variable for the effect of market orientation on the performance of SMEs because the direct influence of market orientation is greater than the performance of SMEs through competitive advantage.